Corporate expropriation from the perspective of non-contestability of ownership structure and corporate governance - Ahmad Husni, Hamzah; Abdul Hadi, Zulkafli (2018)
This study examines the effect of ownership contestability and corporate governance on corporate expropriation in Malaysia. The results of this study show that firms with the presence of only controlling shareholder are strongly influenced corporate expropriation. Firms with higher percentage of controlling shareholder pay lower dividend to their shareholders indicating the possibility of expropriation through profit diversion. In regards to the role of corporate governance, it can be concluded that large board size positively influenced expropriation only in firms with large shareholders. Moreover, foreign board members have a significant influence on expropriation in firms with the presence of large shareholders with and without controlling shareholders. Furthermore, the board remuneration has significant influence on expropriation in firm with the presence of only large shareholders. The outcome contributes towards a better understanding on the monitoring role of corporate ownership as a corporate governance mechanism in alleviating corporate expropriation in Malaysia.